State-of-the-art bibliometric review of library research 2018-2020 in Scopus database / Muslim Ismail@Ahmad … [et al.] - Ismail@Ahmad, Muslim; Alias, Noor Rahmawati; Ab Rahman, Rosmariyati; Hussin@Hussein, Alina (2020)
Three years’ recent library research in eleven academic journals, Library Philosophy and Practice, Serials Librarian, Library Review, Journal of Library Administration, Journal of Academic Librarianship, Library Management, Library Hi Tech, Electronic Library, Library Trends, New Library World, and Reference Librarian were analyzed using bibliometric instrument to describe current research topics in library sciences. This research described state-of-the-art sciences and identified key research themes in library subjects. Total citations retrieved were 1,878 research data ranging from 2018 to 2020. Journals’ ranking in SCImago Journal Ranking and CiteScore were analyzed comparatively and research impact were evaluated by the number of citations received. Co-word analysis was used to extract significant key terms from data collection and citation network analysis identified key papers in respective themes. This research utilized VOSviewer software to visualize library research sciences.